Screening of Sunflower Genotypes for Reaction to Alternaria Leaf Blight Disease across Multi-environments using Pooled Analysis - Asish , K Binodh; Thankappan, Sugitha; Paramasivam, M (Plant Science Today, 2023)
Sunflower (Helianthus annuus L.) is an oilseed crop with potential health benefits as a source of oil and dietary fiber. The productivity of sunflower is hampered by both biotic and abiotic stresses caused due to climate changes. So far, the available gene pool is having moderately resistant lines. In the present study, we evaluated two screening methods by artificially challenging the plants with the causative agent A. helianthi. Significant changes in disease severity have been observed across 160 pre-breeding lines of sunflower, including the susceptible check, Morden in three different seasons. Among the160 pre-breeding lines derived from a mutant population of sunflower cv. Morden, 6.25 and 5.63 % of lines showed less leaf blight disease incidence under in vivo and in vitro environments respectively. Moreover, 44.38 % of the sunflower pre breeding lines demonstrated field tolerance with disease severity in the scale of 5. The promising accessions evaluated in our studies by whole plant assay method and detached leaf technique includes KSFI 19, KSFI 24, KSFI 147, KSFI 56, KSFI 120, KSFI 88, KSFI 152, KSFI 51 and KSFI 115. Therefore, these sunflower lines, could be employed for introgression of resistance genes against leaf blight disease in sunflower cultivars through marker assisted breeding strategies.